2021
DOI: 10.21203/rs.3.rs-904044/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Comparison Benefit between Hydrogen Peroxide and Adrenaline in Tonsillectomy: A Randomized Controlled Study

Abstract: This study aimed to further evaluate the benefit of topical hemostasis agents in tonsillectomy. Towards this goal, we compared the clinical effects of topical application between hydrogen peroxide and adrenaline in tonsillectomy. Overall, 60 patients (120 tonsils) were prospectively enrolled for tonsillectomy between February 2018 and December 2020. The patients were randomly assigned to either the hydrogen peroxide or adrenaline group. Then, tonsillectomy was performed using hydrogen peroxide as a hemostatic … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 16 publications
(18 reference statements)
0
3
0
Order By: Relevance
“…Incidence of postoperative blood loss and transfusion were significantly lower in group H when compared to the control group (47% versus 62%) and (36.5% versus 50%) as shown in table (3).…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…Incidence of postoperative blood loss and transfusion were significantly lower in group H when compared to the control group (47% versus 62%) and (36.5% versus 50%) as shown in table (3).…”
Section: Resultsmentioning
confidence: 86%
“…H2O2 can be used as a chemical hemostasis agent that is easily degraded by tissue catalase to form oxygen and water. It is a widely available topical antiseptic and nontoxic hemostasis agent that produces oxidative burst and local oxygen production (3) .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, hydrogen peroxide has been shown to act as a topical haemostatic agent, thereby temporarily maintaining a bloodless cancellous bed to optimize cement penetration. [2][3][4] Biomechanical studies have investigated the advantage hydrogen peroxide provides in canal preparation. Ackland et al 5 demonstrated a higher tensile load-to-failure when hydrogen peroxide is combined with pulse lavage to treat the intramedullary canal prior to cementing.…”
mentioning
confidence: 99%